The awareness and use of chaperones by patients in an English general practice. Issue 8 (27th July 2010) - Pydah, K L; Howard, J
Abstract : Objective: To ascertain and improve the understanding and use of chaperones among the patients of an English general practice (GP). Background: Doctors have long been advised to have a third party present during intimate physical examinations. Little is known about the understanding of the term in the general population in England and the consequences of this for the promotion and use of chaperones in GP. We audited the understanding and use of chaperones in an English GP. The aim of the study was to increase the awareness of the availability of chaperones in our population. Methods: A questionnaire was given randomly to 100 patients attending the GP surgery. Participants were asked about their awareness of and frequency of requesting a chaperone while undergoing intimate examinations. Based on the initial results, a poster was designed for the waiting room to increase awareness. Data were collected with the same questionnaire to see if the new poster altered surgery attendees understanding and likely subsequent use of chaperones. Results: In the initial audit, 29% of patients were unaware of the term chaperone, and only one person (1%) had ever requested a chaperone. After the introduction of a specially designed poster, the results showed an improvement in awareness from 71% to 89%, and the likely frequency of using a chaperone increased from 1% to 4%. Conclusion: There is a need to improve the understanding of the general population about chaperones if we are to see greater use of chaperones in GP.